Application of microwave oven technology for dehydration of ornamental leaves (Current Horticulture, 2023)
The standardization of microwave oven drying technology for dehydration of ornamental leaves was done. The embedding of leaves  in silica gel and microwave oven drying (720 micro power, i.e. medium high) for 2 min was suitable technique for dehydration of  ornamental leaves of Swietenia mahagoni, Acacia auriculiformis and Hamelia patens leaves. The time of 2.5 min was appropriate for  leaves of Alstonia scholaris, Rosa spp., Hibiscus rosa-sinensis and Bougainvillea glabra, 3 min for Lagerstroemia speciosa and 3.5 min  for Polyalthia longifolia and Ixora chinensis.
Keywords: Microwave oven; Dehydration; Technology; Ornamental leaves; Eco-friendly